PENGARUH PENGURANGAN AIR PADA BEBERAPA MUTU BETON YANG MENGGUNAKAN POLINEX HE - Indriyani Puluhulawa; Alamsyah Alamsyah; Poltak Leonardo Sitinjak; Marganta P. R. Lubis (Racic : Rab Construction Research, 2024)
Concrete with the addition of Polinex HE has a slump value that is twice as large as concrete without Polinex HE. This can lead to segregation during pouring. Therefore, a study was conducted to investigate the effect of reducing the water content in concrete using Polinex HE. The aim of this research was to examine how the reduction in water content affects slump values, concrete density, and concrete quality. A total of 72 cylindrical concrete samples with a diameter of 10 cm and a height of 20 cm were prepared for both K-250 and K-350 concrete. Water reduction variations ranged from 5% to 20% of the water weight, with the addition of Polinex HE at 1% of the cement weight. Testing included slump tests, concrete density measurements, and compressive strength tests at 3 days and 28 days of curing.The results showed that the slump values remained higher compared to concrete without Polinex HE. Concrete density decreased as the water content was reduced. For K-250 concrete, maximum compressive strength was achieved with a 5% reduction in water content, while for K-350 concrete, maximum compressive strength was achieved with a 20% reduction in water content.